2020
DOI: 10.1038/s41598-020-58197-y
|View full text |Cite
|
Sign up to set email alerts
|

A misprocessed form of Apolipoprotein A-I is specifically associated with recurrent Focal Segmental Glomerulosclerosis

Abstract: Apolipoprotein A-Ib (ApoA-Ib) is a high molecular weight form of Apolipoprotein A-I (ApoA-I) found specifically in the urine of kidney-transplanted patients with recurrent idiopathic focal segmental glomerulosclerosis (FSGS). To determine the nature of the modification present in ApoA-Ib, we sequenced the whole APOA1 gene in ApoA-Ib positive and negative patients, and we also studied the protein primary structure using mass spectrometry. No genetic variations in the APOA1 gene were found in the ApoA-Ib positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 47 publications
(62 reference statements)
0
14
0
Order By: Relevance
“…A younger age at diagnosis, severe hypoalbuminaemia and rapid progression to ESKD (for example, within 3 years of diagnosis) are also more common in patients who experience recurrence after transplantation. Apolipoprotein A-Ib, a high-molecular-weight form of apolipoprotein A-I, was recently proposed as a possible biomarker for recurrent forms of podocytopathies after kidney transplantation 224 . Typically, relapses occur in the first 2 weeks after kidney transplantation and often respond to combined treatment with plasma exchange, rituximab and intensified immunosuppression, although the response may be transient 225,226 .…”
Section: Relapse After Transplantationmentioning
confidence: 99%
“…A younger age at diagnosis, severe hypoalbuminaemia and rapid progression to ESKD (for example, within 3 years of diagnosis) are also more common in patients who experience recurrence after transplantation. Apolipoprotein A-Ib, a high-molecular-weight form of apolipoprotein A-I, was recently proposed as a possible biomarker for recurrent forms of podocytopathies after kidney transplantation 224 . Typically, relapses occur in the first 2 weeks after kidney transplantation and often respond to combined treatment with plasma exchange, rituximab and intensified immunosuppression, although the response may be transient 225,226 .…”
Section: Relapse After Transplantationmentioning
confidence: 99%
“…Amongst the several modified ApoA-I forms, ApoA-1b is noted to be present in the urine of recurrent FSGS. ApoA-Ib is a high molecular weight form of ApoA-I that may be associated with a misprocessed form of ApoA-I precursor with no genetic variations in the ApoA-I gene [31]. One study performed a proteomic analysis of serum and urine samples of transplant patients with history of primary FSGS; the results showed the existence of ApoA-Ib exclusively in patients with relapsing FSGS [29].…”
Section: Circulating Permeability Factors Of Fsgsmentioning
confidence: 99%
“…Most recurrences occur early with a median time of 1.5-12 months in primary FSGS [37 && ,45]. The early and high recurrence rates of primary FSGS has been attributed to the presence of a circulating permeability factor in the sera of KTRs, the identity of which has been the subject of ongoing research [42,46]. Savin et al [47] first demonstrated that rats exposed to sera of patients with recurrent FSGS developed albuminuria, while Gallon et al [48] later described a case of rapidly recurrent FSGS in a living donor recipient in which there was a reversal of the histopathologic and clinical features of FSGS in the same allograft after it was explanted and retransplanted into a different recipient without native FSGS.…”
Section: Focal and Segmental Glomerulosclerosismentioning
confidence: 99%